Steel plate, member and manufacturing method thereof

JP7632758B2Active Publication Date: 2025-02-19JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024531140
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-30
Filing Date
2024-01-25
Publication Date
2025-02-19
Estimated Expiration
2044-01-25

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、高強度であり、耐遅れ破壊特性に優れる鋼板、部材およびそれらの製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632758000001
    Figure 0007632758000001
  • Figure 0007632758000002
    Figure 0007632758000002
  • Figure 0007632758000003
    Figure 0007632758000003
Patent Text Reader

Abstract

Provided are a steel sheet and a member that have high strength and excellent resistance to delayed fractures, and production methods for these. The steel sheet contains, in mass%, 0.15% to 0.45% of C, 2.0% or less of Si, 4.0% or less of Mn, 0.10% or less of P, 0.01% or less of S, 0.50% or less of sol. Al, 0.010% or less of N, and 0.0008% to 0.0100% of B, with the remainder consisting of Fe and unavoidable impurities. The steel sheet has a steel structure in which the area ratio of martensite to the whole structure is at least 85% but less than 95%, the area ratio of ferrite to the whole structure is 5% to 15%, and the average crystal grain size of ferrite is 10 μm or less. The number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the formula: A (precipitates / mm2)≤8.5×105×[B].
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel plate such as a high-strength steel plate for cold press forming used in automobiles and the like after undergoing cold press forming, a member using the steel plate, and a method for manufacturing the same. [Background technology]

[0002] In recent years, steel sheets with a tensile strength of 1310 MPa or higher have been increasingly used in automotive frame parts for the purposes of reducing the weight of automobiles and improving collision safety. Also, steel sheets with a tensile strength of 1470 MPa or higher have been increasingly used in bumpers, impact beams, etc.

[0003] When high-strength steel plate with a tensile strength of 1470 MPa or more is formed into a part by cold pressing, delayed fracture may occur due to an increase in residual stress in the part or a deterioration in the delayed fracture resistance of the steel plate itself.

[0004] Here, delayed fracture refers to a phenomenon in which, when a component is placed in a hydrogen intrusion environment while being subjected to high stress, hydrogen infiltrates into the steel plate that constitutes the component, reducing the interatomic bonding strength and causing localized deformation, resulting in microcracks, which then propagate and lead to fracture.

[0005] As a technique for improving delayed fracture resistance, for example, Patent Document 1 describes a method for improving delayed fracture resistance based on the knowledge that delayed fracture resistance can be improved by reducing coarse precipitates that serve as the starting point of delayed fracture, which includes, by mass%, C: 0.13% to 0.40%, Si: 0.02% to 1.5%, Mn: 0.4% to 1.7%, P: 0.030% or less, S: 0.0002% to less than 0.0010%, sol.Al: 0.01% to 0.20%, N: 0.0055% or less, O: 0.0025% or less, Nb: 0. The composition contains 0.002% or more and 0.035% or less and Ti: 0.002% or more and 0.040% or less so as to satisfy the formulas (1) and (2), with the balance being Fe and unavoidable impurities, and the area ratio of martensite and bainite to the entire structure is 95% or more and 100% or less in total, with the balance being one or both of ferrite and retained austenite, the average grain size of prior austenite grains is more than 5 μm, and the number of inclusions with a major axis length of 20 to 80 μm that satisfy the following conditions is 5 / mm 2 The document discloses a high-strength steel plate having excellent resistance to delayed fracture, characterized by having a steel structure as described below and a tensile strength of 1320 MPa or more. [%Ti]+[%Nb]>0.007 (1) [% Ti] × [% Nb] 2 ≦7.5×10 -6 (2) Here, [%Nb] and [%Ti] represent the Nb and Ti contents (%).

[0006] Patent Document 2 also describes a steel containing, by mass%, C: 0.05 to 0.30%, Si: 2.0% or less (including 0%), Mn: more than 0.1% and 2.8% or less, P: 0.1% or less, S: 0.005% or less, N: 0.01% or less, Al: 0.01 to 0.50% or less, and one or more of Nb, Ti, and Zr, each of which is 0.01% or more in total, and [%C]-[%Nb] / 92.9×12-[% The composition satisfies the relationship [%Ti] / 47.9×12-[%Zr] / 91.2×12>0.03, with the balance being iron and unavoidable impurities, the area ratio of tempered martensite is 50% or more (including 100%), the balance being ferrite, and the distribution state of precipitates in the tempered martensite is such that precipitates having a circle equivalent diameter of 1 to 10 nm are within the range of 1 μm in the tempered martensite. 2 Precipitates containing one or more of Nb, Ti and Zr are present in a number of 20 or more per 1000 mm diameter and have a circle equivalent diameter of 20 nm or more. 2 This paper discloses a high-strength cold-rolled steel sheet having excellent hydrogen embrittlement resistance and workability, characterized in that the average grain size of ferrite surrounded by high-angle grain boundaries with a crystal orientation difference of 15° or more is 5 μm or less and that the number of grains per square inch is 10 or less. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6388085 [Patent Document 2] Patent No. 4712882 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the conventional technology is not sufficient to ensure a tensile strength TS of 1470 MPa or more while also providing excellent resistance to delayed fracture, and there has been a demand for the establishment of a new technology.

[0009] The present invention has been made to solve such problems, and has an object to provide a steel plate, a member, and a manufacturing method thereof, which have a tensile strength of 1470 MPa or more (TS≧1470 MPa) and excellent delayed fracture resistance.

[0010] The term "excellent delayed fracture resistance" means that the material is judged to have excellent delayed fracture resistance based on the following evaluation. (1) First, a rectangular test piece measuring 100 mm in the direction perpendicular to the rolling direction and 30 mm in the rolling direction is taken from the widthwise end of the obtained steel sheet (coil) at a position 1 / 4 of the coil width. (2) The end surface on the long side with a length of 100 mm is cut out by shearing, and then while in the sheared state (without machining to remove burrs), it is bent so that the burrs are on the outer periphery of the bend. The test piece is fixed with bolts while maintaining the shape of the test piece at the time of bending. The clearance for shear processing is 13%, and the rake angle is 1°. The bending process is performed so that the tip bending radius is 10 mm and the inner angle of the bending apex is 90 degrees (V-bend). The punch used has a tip radius equal to the tip bending radius R mentioned above and is U-shaped (the tip R part is semicircular and the punch body is 2R thick), and the die used has a corner R of 30 mm. The depth to which the punch presses into the steel plate is adjusted to form the tip bending angle (the angle at the inside of the apex of the bend) to 90 degrees (V-shape). The test piece is clamped and tightened with a hydraulic jack so that the distance between the flange ends of the straight pieces when bent is the same as when they were bent (to cancel out the opening in the straight pieces caused by springback), and the bolts are fastened in this state. The bolts are fixed through elliptical holes (minor axis 10 mm, major axis 15 mm) that have been previously provided 10 mm inward from the short edge of the rectangular test piece. (3) The obtained bolted test specimens are immersed in a solution prepared by mixing 0.1% by mass of ammonium thiocyanate aqueous solution and McIlvaine buffer solution in a mass ratio of 1:1 and adjusting the pH to 8.0 and 7.4, respectively, to carry out a delayed fracture resistance evaluation test. At this time, the temperature of the solution is 20°C, and the test specimens are immersed in a solution of 1 cm2 surface area and adjusted to 8.0 and 7.4, respectively.3 The volume of each liquid is 20 ml. (4) After 48 hours, the presence or absence of visually visible cracks (length 1 mm or more) was confirmed, and those in which no cracks were observed in the solution adjusted to pH 8.0 were judged to have excellent delayed fracture resistance. Furthermore, those in which no cracks were observed in the solution adjusted to pH 7.4 were judged to have particularly excellent delayed fracture resistance. [Means for solving the problem]

[0011] The present inventors have conducted extensive research to solve the above problems and have found that delayed fracture resistance can be significantly improved by satisfying all of the following conditions: i) The area ratio of martensite is 85% or more and less than 95%. ii) The area ratio of ferrite is 5% or more and 15% or less, and the average crystal grain size of ferrite is 10 μm or less. iii) The number density A of precipitates with a circular equivalent diameter of 500 nm or more satisfies the following condition: A (pieces / mm 2 )≦ 8.5×10 5 ×[B] Here, [B] represents the B content (mass %).

[0012] The present invention has been completed through further investigation based on the above findings, and the gist of the present invention is as follows. [1] In mass percent, C: 0.15% or more and 0.45% or less, Si: 2.0% or less, Mn: 4.0% or less, P: 0.1% or less, S: 0.01% or less, Sol.Al: 0.5% or less, N: 0.010% or less, B: Contains 0.0008% or more and 0.0100% or less, The balance is Fe and unavoidable impurities. The area ratio of martensite to the entire structure is 85% or more and less than 95%, The area ratio of ferrite to the entire structure is 5% or more and 15% or less, The steel has a steel structure in which the average grain size of ferrite is 10 μm or less, A steel sheet in which the number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula (1). A (pieces / mm 2 )≦ 8.5×10 5 ×[B]...Equation (1) Here, [B] represents the B content (mass %). [2] The steel plate according to [1], wherein 50% or more of the ferrite is precipitated on prior austenite grain boundaries, in terms of area ratio. [3] The component composition further includes, in mass%, Cu: 1.00% or less, Cr: 1.00% or less, Nb: 0.10% or less, Ti: 0.10% or less, V: 0.50% or less, Mo: 0.50% or less Ni: 1.00% or less, Sb: 0.10% or less, Sn: 0.10% or less, As: 0.10% or less, Ta: 0.10% or less, Ca: 0.020% or less, Mg: 0.020% or less, Zn: 0.020% or less, Co: 0.020% or less, Zr: 0.020% or less, W: 0.020% or less, The steel plate according to [1] or [2], containing one or more selected from REM: 0.020% or less. [4] The steel sheet according to any one of [1] to [3], which has a plating layer on the surface of the steel sheet. [5] A member made using the steel plate according to any one of [1] to [4]. [6] A steel slab having the composition described in [1] or [3] is heated and held at a temperature of 1100°C or higher for 30 minutes or more at the slab surface temperature, and then Hot finish rolling is performed under the conditions of a residence time of 20 seconds or more and 150 seconds or less at 900 to 1000 ° C and a finish rolling temperature of 850 ° C or more. Cooling is performed at an average cooling rate of 40°C / sec or more in the range from the finish rolling temperature to 650°C, After that, the hot-rolled steel sheet is produced by coiling at a coiling temperature of 650°C or less. The hot-rolled steel sheet is cold-rolled at a rolling reduction of 40% or more to obtain a cold-rolled steel sheet; The annealing temperature is set to 830 to 950 ° C., and the cold-rolled steel sheet is heated from 400 ° C. to the annealing temperature at an average heating rate of 1.0 ° C. / second or more, After holding at the annealing temperature for 10 seconds or more and 600 seconds or less, Cooling from the annealing temperature to Ar3 point at an average cooling rate of 10 ° C. / sec or more, Cool from Ar3 point to (Ar3 point - 80℃) at an average cooling rate of 1 to 10℃ / sec. Cool from (Ar3 point -80℃) to a cooling stop temperature of 260℃ or less at an average cooling rate of 10℃ / sec or more, This is followed by continuous annealing at a holding temperature of 150 to 260°C for 20 to 1,500 seconds. [7] The method for producing a steel sheet according to [6], further comprising the step of: subjecting a surface of the steel sheet to a plating treatment after the continuous annealing. [8] A method for producing a component, comprising the step of subjecting the steel plate according to any one of [1] to [4] to at least one of forming and joining to form a component. Effect of the Invention

[0013] According to the present invention, there are provided a steel plate, a member and a method for producing the same which are high in strength and excellent in delayed fracture resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described.

[0015] The steel sheet of the present invention has a composition containing, by mass%, C: 0.15% or more and 0.45% or less, Si: 2.0% or less, Mn: 4.0% or less, P: 0.10% or less, S: 0.01% or less, sol.Al: 0.50% or less, N: 0.01% or less, B: 0.0008% or more and 0.0100% or less, with the balance being Fe and unavoidable impurities, has a structure in which the area ratio of martensite to the entire structure is 85% or more and less than 95%, the area ratio of ferrite to the entire structure is 5% or more and 15% or less, and the average crystal grain size of ferrite is 10 μm or less, and the number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula (1). A (pieces / mm 2 )≦ 8.5×10 5 ×[B]...Equation (1) Here, [B] represents the B content (mass %).

[0016] Ingredient composition The reasons for limiting the ranges of the chemical composition of the steel sheet of the present invention will be explained below. Note that % regarding the content of each component is "mass %".

[0017] C: 0.15% or more and 0.45% or less C is contained to increase the strength of martensite and obtain a tensile strength of 1470 MPa or more (hereinafter, also referred to as TS≧1470 MPa). Therefore, in order to obtain a desired TS, the C content is set to 0.15% or more. From the viewpoint of reducing the weight of automotive frame parts by increasing the strength, the C content is preferably 0.20% or more, and more preferably 0.25% or more. On the other hand, if an excessive amount of C is added, the formation of ferrite is excessively suppressed, and the desired area ratio of ferrite cannot be obtained. Therefore, the C content is set to 0.45% or less. The C content is preferably 0.40% or less, and more preferably 0.35% or less.

[0018] Si: 2.0% or less Silicon inhibits the formation of film-like carbides when tempering at temperatures above 200°C, inhibiting the decrease in strength and the deterioration of delayed fracture resistance. Although there is no lower limit for the silicon content, it is desirable for silicon to be contained in an amount of 0.02% or more. The silicon content is preferably 0.10% or more, and more preferably 0.20% or more. On the other hand, excessive addition of Si leads to deterioration of delayed fracture resistance due to segregation of Si. Therefore, the Si content is set to 2.0% or less (including 0%). The Si content is preferably 1.5% or less, and more preferably 1.0% or less.

[0019] Mn:4.0% or less Mn is an element effective in improving the hardenability of steel. Although there is no lower limit for the Mn content, in order to stably obtain a desired area ratio of martensite, the Mn content is desirably 0.2% or more. The Mn content is preferably 0.5% or more. On the other hand, if Mn is added in excess, the formation of ferrite is excessively suppressed, and the desired ferrite area ratio cannot be obtained. Therefore, the Mn content is set to 4.0% or less. The Mn content is preferably 3.0% or less, and more preferably 1.7% or less.

[0020] P:0.10% or less P segregates at grain boundaries and reduces grain boundary strength, which leads to a deterioration in delayed fracture resistance. Therefore, the P content is set to 0.10% or less. The P content is preferably 0.05% or less, more preferably 0.02% or less, and further preferably 0.01% or less. There is no lower limit for the P content, but the lower limit that is currently industrially feasible is 0.002%. Therefore, the P content is preferably set to 0.002% or more.

[0021] S: 0.01% or less S forms coarse inclusions with Mn, which become the starting point of delayed fracture, leading to deterioration of delayed fracture resistance. Therefore, the S content is set to 0.01% or less. The S content is preferably 0.003% or less, more preferably 0.0015% or less, and further preferably 0.0008% or less. There is no lower limit, but the lower limit currently industrially feasible is 0.0002%. Therefore, the S content is preferably set to 0.0002% or more.

[0022] Sol.Al: 0.50% or less Al is contained to perform sufficient deoxidation and reduce inclusions in steel. There is no particular lower limit for sol.Al, but in order to perform stable deoxidation, it is desirable for the sol.Al content to be 0.005% or more. The sol.Al content is more preferably 0.01% or more, and even more preferably 0.02% or more. On the other hand, if the sol.Al content exceeds 0.50%, the cementite formed during coiling is difficult to dissolve in the annealing process, the number density A of the precipitates cannot be set within the desired range, and the delayed fracture resistance is significantly deteriorated. Therefore, the sol.Al content is set to 0.50% or less. The sol.Al content is preferably 0.20% or less, and more preferably 0.05% or less.

[0023] N: 0.010% or less N forms precipitates such as AlN, which become the starting point of delayed fracture, thereby deteriorating the delayed fracture resistance. In particular, if N exceeds 0.010%, the number density A of the precipitates cannot be set within the desired range, and the delayed fracture resistance is significantly deteriorated. Therefore, the N content is set to 0.010% or less. The N content is preferably set to 0.005% or less. Although no lower limit is specified, the lower limit currently industrially feasible is 0.0006%. Therefore, the N content is preferably set to 0.0006% or more.

[0024] B: 0.0008% or more and 0.0100% or less B is an element that improves the hardenability of steel, and has the effect of forming a specified area ratio of martensite even with a small Mn content. In addition, B segregates to grain boundaries to increase the binding strength of the grain boundaries and suppresses the segregation of P that reduces grain boundary strength. In order to obtain the desired delayed fracture resistance due to these actions, the B content is set to 0.0008% or more. The B content is preferably 0.0015% or more, and more preferably 0.0020% or more. On the other hand, when B is added in excess, Fe 23 It was found that the formation of (C,B)6 and BN, which become the starting point of delayed fracture, rather reduces the delayed fracture resistance. Therefore, in order to obtain the effect of improving the delayed fracture resistance by adding B, it is necessary to add B while keeping the number density A of the precipitates within a desired range. If the B content exceeds 0.0100%, it is difficult to reduce the B-based precipitates even by controlling the hot rolling conditions and annealing conditions, and the number density A of the precipitates cannot be kept within a desired range. Therefore, the B content is set to 0.0100% or less. The B content is preferably 0.0080% or less, more preferably 0.0060% or less.

[0025] The composition of the steel sheet in the present invention contains the above-mentioned elemental elements as basic components, with the balance being iron (Fe) and unavoidable impurities. Here, it is preferable that the steel sheet of the present invention has a composition containing the above-mentioned basic components, with the balance being iron (Fe) and unavoidable impurities.

[0026] In the present invention, the component composition may contain the following. By mass%, one or more selected from the following: Cu: 1.00% or less, Cr: 1.00% or less, Nb: 0.10% or less, Ti: 0.10% or less, V: 0.50% or less, Mo: 0.50% or less, Ni: 1.00% or less, Sb: 0.10% or less, Sn: 0.10% or less, As: 0.10% or less, Ta: 0.10% or less, Ca: 0.020% or less, Mg: 0.020% or less, Zn: 0.020% or less, Co: 0.020% or less, Zr: 0.020% or less, W: 0.020% or less, REM: 0.020% or less

[0027] Cu:1.00% or less Cu has the effect of improving the corrosion resistance of the steel sheet, reducing hydrogen penetration into the steel sheet, and improving delayed fracture resistance. Although there is no lower limit for the Cu content, in order to obtain these effects, the Cu content is desirably 0.01% or more. The Cu content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if Cu is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Cu is contained, the Cu content is set to 1.00% or less. The Cu content is preferably 0.50% or less, and more preferably 0.30% or less.

[0028] Cr:1.00% or less Cr is an element effective in improving the hardenability of steel. Cr can be added to stably obtain a desired structure. There is no particular lower limit for the Cr content, but in order to obtain this effect, the Cr content is preferably 0.01% or more. The Cr content is more preferably 0.05% or more, and even more preferably 0.10% or more. On the other hand, if Cr is added in excess, the dissolution of cementite during annealing is delayed, and a large amount of undissolved cementite remains, making it impossible to set the number density A of precipitates within a desired range, and the delayed fracture resistance is deteriorated. Therefore, when Cr is contained, the Cr content is set to 1.00% or less. The Cr content is preferably 0.50% or less, and more preferably 0.30% or less.

[0029] Nb: 0.10% or less Nb has the effect of forming fine precipitates such as NbC in steel, thereby refining the prior austenite grain size through a pinning effect, and improving delayed fracture resistance. Although there is no lower limit for the Nb content, in order to obtain the effect of improving delayed fracture resistance, the Nb content is desirably 0.005% or more. The Nb content is preferably 0.01% or more. On the other hand, if Nb is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Nb is contained, the Nb content is set to 0.10% or less. The Nb content is preferably 0.08% or less, and more preferably 0.06% or less.

[0030] Ti: 0.10% or less Ti forms fine precipitates such as TiC in steel, which refines the prior austenite grain size through a pinning effect, and has the effect of improving delayed fracture resistance. Although there is no lower limit for the Ti content, in order to obtain this effect, the Ti content is desirably 0.005% or more. The Ti content is preferably 0.01% or more. On the other hand, if Ti is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates because the precipitates cannot be made to fall within the desired range. Therefore, when Ti is contained, the Ti content is set to 0.10% or less. The Ti content is preferably 0.08% or less, and more preferably 0.06% or less.

[0031] V: 0.50% or less V has the effect of generating fine carbides containing V that become hydrogen trapping sites, thereby improving delayed fracture resistance. In addition, by forming fine precipitates, the prior austenite grain size is refined by the pinning effect, thereby improving delayed fracture resistance. Although there is no lower limit for the V content, in order to obtain such effects, it is desirable that the V content is 0.003% or more. The V content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, if V is added in excess, the number of coarse precipitates increases, the number density A of the precipitates cannot be set within the desired range, and the delayed fracture resistance deteriorates. Therefore, when V is contained, the V content is set to 0.50% or less. The V content is preferably 0.20% or less, more preferably 0.10% or less, and further preferably 0.06% or less.

[0032] Mo: 0.50% or less Mo has the effect of improving delayed fracture resistance by forming fine carbides containing Mo that become hydrogen trapping sites. In addition, by forming fine precipitates, the prior austenite grain size is refined by the pinning effect, and delayed fracture resistance is improved. Although there is no lower limit for the Mo content, in order to obtain the effect of improving delayed fracture resistance, the Mo content is desirably 0.003% or more. The Mo content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, if Mo is added in excess, the number of coarse precipitates increases, the number density A of the precipitates cannot be set within the desired range, and the delayed fracture resistance deteriorates. Therefore, when Mo is contained, the Mo content is set to 0.50% or less. The Mo content is preferably 0.20% or less, and more preferably 0.10% or less.

[0033] Ni: 1.00% or less Ni has the effect of improving the corrosion resistance of steel sheets, suppressing hydrogen penetration into the steel sheets, and improving delayed fracture resistance. Ni is also an element effective in improving the hardenability of steel, and can be added to stably obtain a desired structure. Although there is no lower limit for the Ni content, in order to obtain such effects, it is desirable that the Ni content is 0.01% or more. The Ni content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if Ni is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates because the precipitates cannot be made in the desired range. Therefore, when Ni is contained, the Ni content is set to 1.00% or less. The Ni content is preferably 0.50% or less, and more preferably 0.30% or less.

[0034] Sb: 0.10% or less Sb suppresses oxidation and nitridation of the surface layer of the steel sheet, and contributes to increasing strength and improving delayed fracture resistance. Although there is no lower limit for the Sb content, in order to obtain such effects as increasing strength and improving delayed fracture resistance, the Sb content is desirably 0.002% or more. The Sb content is preferably 0.004% or more, and more preferably 0.006% or more. On the other hand, if Sb is added in excess, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Sb is contained, the Sb content is set to 0.10% or less. The Sb content is preferably 0.05% or less, and more preferably 0.02% or less.

[0035] Sn: 0.10% or less Sn suppresses oxidation and nitridation of the surface layer of the steel sheet, and contributes to increasing strength and improving delayed fracture resistance. Although there is no lower limit for the Sn content, in order to obtain such effects as increasing strength and improving delayed fracture resistance, the Sn content is desirably 0.002% or more. The Sn content is preferably 0.004% or more, and more preferably 0.006% or more. On the other hand, if Sn is added in excess, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Sn is contained, the Sn content is set to 0.10% or less. The Sn content is preferably 0.05% or less, and more preferably 0.02% or less.

[0036] As: 0.10% or less As has the effect of increasing the strength of steel. Although there is no lower limit for the As content, in order to obtain the effect of increasing the strength of steel, the As content is desirably 0.002% or more. The As content is preferably 0.004% or more, and more preferably 0.006% or more. On the other hand, if As is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates because the precipitates cannot be made to fall within the desired range. Therefore, when As is contained, the As content is set to 0.10% or less. The As content is preferably 0.05% or less, and more preferably 0.02% or less.

[0037] Ta: 0.10% or less Ta has the effect of increasing the strength of steel. Although there is no lower limit for the Ta content, in order to obtain the effect of increasing the strength of steel, the Ta content is desirably 0.002% or more. The Ta content is preferably 0.004% or more, and more preferably 0.006% or more. On the other hand, if Ta is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Ta is contained, the Ta content is set to 0.10% or less. The Ta content is preferably 0.05% or less, and more preferably 0.02% or less.

[0038] Ca: 0.020% or less Ca reduces the initiation points of delayed fracture by making the shape of sulfides spheroidal, thereby improving delayed fracture resistance. In order to obtain the effect of improving delayed fracture resistance, the Ca content is desirably 0.0002% or more. The Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if Ca is added in excess, the number of coarse precipitates increases, the number density A of the precipitates cannot be set within the desired range, and the delayed fracture resistance deteriorates. Therefore, when Ca is contained, the Ca content is set to 0.020% or less. The Ca content is preferably 0.015% or less, and more preferably 0.010% or less.

[0039] Mg: 0.020% or less Mg reduces the initiation points of delayed fracture by making the shape of sulfides spheroidal, thereby improving delayed fracture resistance. In order to obtain the effect of improving delayed fracture resistance, the Mg content is desirably 0.0002% or more. The Mg content is preferably 0.001% or more, and more preferably 0.003% or more. On the other hand, if Mg is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates because the precipitates cannot be made to have a desired range. Therefore, when Mg is contained, the Mg content is set to 0.020% or less. The Mg content is preferably 0.015% or less, and more preferably 0.010% or less.

[0040] Zn: 0.020% or less Zn improves delayed fracture resistance by refining the prior austenite grain size and spheroidizing the inclusion shape. In order to obtain the effect of improving delayed fracture resistance, the Zn content is desirably 0.001% or more. The Zn content is preferably 0.003% or more. On the other hand, if Zn is added in excess, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Zn is contained, the Zn content is set to 0.020% or less. The Zn content is preferably 0.015% or less, and more preferably 0.010% or less.

[0041] Co:0.020% or less Co improves delayed fracture resistance by refining the prior austenite grain size and spheroidizing the inclusion shape. In order to obtain the effect of improving delayed fracture resistance, the Co content is desirably 0.001% or more. The Co content is preferably 0.003% or more. On the other hand, if Co is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Co is contained, the Co content is set to 0.020% or less. The Co content is preferably 0.015% or less, and more preferably 0.010% or less.

[0042] Zr: 0.020% or less Zr improves delayed fracture resistance by refining the prior austenite grain size and spheroidizing the inclusion shape. In order to obtain the effect of improving delayed fracture resistance, the Zr content is desirably 0.001% or more. The Zr content is preferably 0.003% or more. On the other hand, if Zr is added in excess, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when Zr is contained, the Zr content is set to 0.020% or less. The Zr content is preferably 0.015% or less, and more preferably 0.010% or less.

[0043] W: 0.020% or less W improves delayed fracture resistance by refining the prior austenite grain size through the formation of precipitates. In order to obtain the effect of improving delayed fracture resistance, the W content is desirably 0.001% or more. The W content is preferably 0.003% or more. On the other hand, if W is added excessively, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when W is contained, the W content is set to 0.020% or less. The W content is preferably 0.015% or less, and more preferably 0.010% or less.

[0044] REM: 0.020% or less REM also contributes to improving delayed fracture resistance by spheroidizing inclusions. In order to obtain the effect of improving delayed fracture resistance, the REM content is desirably 0.0002% or more. The REM content is preferably 0.001% or more, and more preferably 0.003% or more. On the other hand, if REM is added in excess, the number density A of the precipitates increases, and the delayed fracture resistance deteriorates. Therefore, when REM is contained, the REM content is set to 0.020% or less. The REM content is preferably 0.015% or less, and more preferably 0.010% or less. In the present invention, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably La and / or Ce.

[0045] When the optional element is contained in an amount less than the preferable lower limit, the optional element is considered to be contained as an unavoidable impurity.

[0046] steel structure The steel structure of the steel plate of the present invention has the following configuration. (Configuration 1) The area ratio of martensite to the entire structure is 85% or more and less than 95%, the area ratio of ferrite to the entire structure is 5% or more and 15% or less, and the average crystal grain size of ferrite is 10 μm or less. (Configuration 2) The number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula (1). A (pieces / mm 2 )≦ 8.5×10 5 ×[B]...Equation (1) Here, [B] represents the B content (mass %).

[0047] Furthermore, by providing the following configuration in addition to (Configuration 1) and (Configuration 2), even better delayed fracture resistance can be obtained. (Configuration 3) In terms of area ratio, 50% or more of the ferrite is ferrite precipitated on prior austenite grain boundaries.

[0048] Each component will be described below.

[0049] (Configuration 1) Area ratio of martensite: 85% or more and less than 95%, area ratio of ferrite: 5% or more and 15% or less, average grain size of ferrite: 10 μm or less In the present invention, by making martensite the main phase, it is possible to realize a high strength of TS≧1470 MPa. In order to obtain the effect of realizing such high strength, the area ratio of martensite needs to be 85% or more. The area ratio of martensite is preferably 88% or more. It was also found that excellent delayed fracture resistance can be obtained by forming martensite as the main phase and ferrite with an area ratio of 5% to 15%. In order to obtain excellent delayed fracture resistance, the area ratio of martensite is less than 95% and the area ratio of ferrite is 5% or more. The area ratio of martensite is preferably less than 93%, and the area ratio of ferrite is preferably 7% or more. On the other hand, excessive generation of ferrite reduces the strength and deteriorates the delayed fracture resistance. Therefore, in order to stably obtain excellent delayed fracture resistance such as TS≧1470MPa, the area ratio of ferrite is set to 15% or less. The area ratio of ferrite is preferably 12% or less.

[0050] In the present invention, the morphology of ferrite is also controlled in order to obtain the effect of improving delayed fracture resistance by 5% to 15% ferrite. If the ferrite is coarse, the effect of improving delayed fracture resistance by ferrite cannot be obtained, and the delayed fracture resistance is rather deteriorated by the generation of ferrite. In order to obtain the effect of improving delayed fracture resistance by ferrite, the average crystal grain size of ferrite is set to 10 μm or less. The average crystal grain size of ferrite is preferably 6 μm or less, and more preferably 4 μm or less. On the other hand, if the ferrite is too fine, the effect of improving delayed fracture resistance may not be sufficiently obtained. Therefore, the average crystal grain size of ferrite is preferably 0.5 μm or more, and more preferably 1.0 μm or more.

[0051] In addition, when it contains structures other than martensite and ferrite, the balance is preferably composed of bainite, residual austenite (residual γ), and pearlite. Other than these structures, it may be a small amount of carbides, sulfides, nitrides, and oxides. The area ratio of the remaining structure is 10% or less, preferably 5% or less, and more preferably 3% or less. The balance structure may be 0%, i.e., the steel structure may consist of martensite and ferrite. Martensite also includes martensite that has undergone self-tempering during continuous cooling, as well as martensite that has not undergone tempering by staying at approximately 150°C or higher for a certain period of time.

[0052] (Configuration 2) The number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula. A (pieces / mm 2 )≦ 8.5×10 5 ×[B]...Equation (1) Here, [B] represents the B content (mass %). In order to suppress delayed fracture in steel with high strength of TS≧1470MPa, it is necessary to control the area ratio of martensite and ferrite and the average grain size of ferrite, as well as to strengthen the grain boundaries with B and suppress intergranular fracture. However, simply increasing the B content increases the amount of Fe, which is the starting point of delayed fracture, as well as the grain boundary segregation B. 23 It was found that this actually reduces the delayed fracture resistance because it also increases B-based precipitates mainly composed of (C,B)6. The inventors have discovered that it is possible to simultaneously improve the delayed fracture resistance due to grain boundary strengthening of B and suppress fracture initiated by precipitates by reducing the number density A of precipitates with a circle equivalent diameter of 500 nm or more through control of hot rolling conditions, etc., and achieving the following conditions: A (pieces / mm 2 )≦ 8.5×10 5 ×[B] The number density A of the precipitates is preferably A (particles / mm 2 )≦ 6.5×10 5 × [B], and more preferably, A (pieces / mm 2 )≦ 5.0×105 ×[B]. In the present invention, the lower limit of A is not particularly limited, and A may be 0. 2 ) ≥ 0.5 × 10 5 ×[B] may also be used.

[0053] (Configuration 3) In terms of area ratio, 50% or more of the ferrite is ferrite precipitated on prior austenite grain boundaries. The main methods for dispersing ferrite in martensite are to hold the material in the two-phase region of austenite and ferrite and then transform the austenite into martensite by quenching, or to hold the material in the single-phase region of austenite and then hold it in the ferrite formation temperature region to form ferrite, and then transform the remaining austenite into martensite by quenching. The ferrite formed by holding in the austenite single phase region and then holding in the ferrite formation temperature region is called proeutectoid ferrite, and since it is formed preferentially on the grain boundaries, it suppresses grain boundary fracture, and is particularly effective in improving delayed fracture resistance. By making ferrite precipitated on the prior austenite grain boundaries 50% or more of the total ferrite amount, a significant improvement effect on delayed fracture resistance can be obtained. Therefore, it is desirable that the area ratio of ferrite precipitated on the prior austenite grain boundaries to the total ferrite amount is 50% or more. Preferably, the area ratio of ferrite precipitated on the prior austenite grain boundaries to the total ferrite amount is 70% or more, and more preferably, the area ratio of ferrite precipitated on the prior austenite grain boundaries to the total ferrite amount is 90% or more. The area ratio of ferrite precipitated on the prior austenite grain boundaries to the total ferrite amount may be 100%.

[0054] The method for measuring each component in the above steel structure will be described below. The area ratios of martensite, bainite, and ferrite are measured by polishing an L-section of a steel plate (a section that is parallel to the rolling direction and perpendicular to the steel plate surface (hereinafter also referred to as a perpendicular section parallel to the rolling direction)) and corroding it with nital, and observing four fields of view in an area of ​​50 μm × 65 μm at a magnification of 2000 times using an SEM at a position 1 / 4 of the thickness from the steel plate surface, and performing image analysis on the photographed structure. Here, martensite and bainite refer to structures that appear gray or white in SEM. On the other hand, ferrite is a region that appears in black contrast in SEM. Note that martensite and bainite contain trace amounts of carbides, nitrides, sulfides, and oxides inside, but since it is difficult to exclude these, the area ratio of the region including these is taken as the area ratio.

[0055] Here, bainite has the following characteristics. It has an aspect ratio of 2.5 or more, a plate-like shape, and is a slightly black structure compared to martensite. The width of the above plates is 0.3 to 1.7 μm. The distribution density of carbides with diameters of 10 to 200 nm inside the bainite is 0 to 3 pieces / μm. 2 It is.

[0056] The amount of retained austenite (retained gamma) is measured by chemically polishing the surface of the steel sheet with oxalic acid for 200 μm, and then measuring the sheet surface using the X-ray diffraction intensity method. It is calculated from the integrated intensity of the (200)α, (211)α, (220)α, (200)γ, (220)γ, and (311)γ diffraction peaks measured with Mo-Kα radiation.

[0057] The average grain size of ferrite is measured by polishing the L-section of the steel sheet (a vertical section parallel to the rolling direction) and corroding it with nital, observing 10 fields of view in an area of ​​50 μm × 65 μm at a magnification of 2000 times with an SEM at a position 1 / 4 thickness from the steel sheet surface, and analyzing the photographed structure to determine the circle equivalent diameter. The circle equivalent diameter refers to the diameter of a perfect circle having an area of ​​a region judged to be ferrite from the SEM photograph. The value obtained by dividing the sum of the above diameters in the 10 fields of view by the number of ferrite particles whose diameters were measured is regarded as the average grain size of ferrite.

[0058] The method for measuring the area ratio of ferrite precipitated on the prior austenite grain boundaries is as follows. First, the L-section of the steel plate is mirror-polished using colloidal silica vibration polishing, and then electron backscatter diffraction (EBSD) measurements are performed to obtain local crystal orientation data for 10 fields of view at a 1 / 4 thickness position from the steel plate surface. The step size is 0.10 μm, and the measurement area is 50 μm x 50 μm. After cleanup processing using analysis software: OIMAnalysis 7, the obtained local orientation data is analyzed to determine the prior austenite grain boundaries. The clean-up process replaces the orientation and CI value of pixels with a CI value of 0.2 or less with that of the neighboring pixel with the highest CI value. Specifically, the cleanup process is performed using the Neighbor CI Correlation function of the analysis software with the parameter Minimum Coufidence Index set to 0.2. A map of grain boundaries having a crystal orientation difference of 20° or more and 50° or less is created, and these interfaces are determined to be prior austenite grain boundaries. After EBSD measurement, the L-section of the steel plate is etched with nital and the same 10 fields of view as those used for EBSD are photographed with an SEM at a magnification of 3000x. When the photographed SEM image is overlaid on the prior austenite grain boundary map of the same field of view, the ferrite present on the prior austenite grain boundaries is identified and the area ratio is measured. One method for observing the same field of view using EBSD and SEM is to make an indentation with a Vickers hardness tester at the observation position on the steel plate in advance, and use this as a marker to mark the observation position.

[0059] The number density A of precipitates with a circle equivalent diameter of 500 nm or more is measured after polishing the L cross section (vertical cross section parallel to the rolling direction) of the steel sheet, in the region from the 1 / 5 position to the 4 / 5 position of the sheet thickness of the steel sheet, that is, in the region from the 1 / 5 position of the sheet thickness from the steel sheet surface to the 4 / 5 position, including the center of the sheet thickness, within 2 mm 2The area is photographed continuously with an SEM, and the number of such precipitates is counted from the photographed SEM photographs. The magnification for photographing is 2000x. When analyzing the components of individual inclusion particles, each inclusion particle is magnified 10000x and the above precipitates are analyzed. Here, precipitates with a circle equivalent diameter of 500nm or more are classified as Fe 23 (C,B)6 is a precipitate containing B. The presence or absence of a B peak is examined by elemental analysis using energy dispersive X-ray spectroscopy (EDS) at an accelerating voltage of 3 kV. If a B peak is present, it is determined that the above precipitate is present. The circle equivalent diameter refers to the diameter of a perfect circle having the area of ​​each precipitate calculated from an SEM photograph.

[0060] Tensile strength (TS): 1470MPa or more When the tensile strength of the steel plate is 1470 MPa or more, the delayed fracture resistance is significantly deteriorated. In this respect, one of the features of the present invention is that the delayed fracture resistance is good even when the tensile strength is 1470 MPa or more. From the viewpoint of weight reduction of automotive frame parts, the tensile strength is preferably 1700 MPa or more. The tensile strength of the steel plate of the present invention may be 2100 MPa or less. The tensile strength of the steel plate of the present invention may be 1900 MPa or less. The tensile strength of the steel plate of the present invention may be 1800 MPa or less. The steel plate of the present invention can obtain extremely excellent delayed fracture resistance by having a tensile strength of 1800 MPa or less. The steel plate of the present invention can obtain extremely excellent delayed fracture resistance even if the steel plate of the present invention has a tensile strength of more than 1800 MPa and not more than 1900 MPa, by having an area ratio of ferrite precipitated on prior austenite grain boundaries to the total ferrite of 50% or more.

[0061] The tensile strength can be measured by cutting a JIS No. 5 tensile test piece at the 1 / 4 position of the coil width so that the direction perpendicular to the rolling is the longitudinal direction, and conducting a tensile test in accordance with JIS Z2241 (2022).

[0062] The above-mentioned steel sheet of the present invention may be a steel sheet having a plating layer on the surface. The plating layer may be Zn plating or plating of other metals. In addition, it may be either a hot-dip plating layer or an electroplating layer.

[0063] Next, a method for producing a steel sheet according to the present invention will be described. The method for producing a steel sheet of the present invention comprises holding a steel slab having the above-mentioned composition at a heating holding temperature of 1100°C or more for 30 minutes or more at a slab surface temperature, hot finish rolling under conditions of a residence time at 900-1000°C of 20 to 150 seconds and a finish rolling temperature of 850°C or more, cooling at an average cooling rate of 40°C / sec or more in the range from the finish rolling temperature to 650°C, and then coiling at a coiling temperature of 650°C or less to obtain a hot rolled steel sheet, cold rolling the hot rolled steel sheet at a rolling reduction of 40% or more to obtain a cold rolled steel sheet, and annealing the hot rolled steel sheet at an annealing temperature of 83°C or more. The annealing temperature is set to 0 to 950°C, and the cold-rolled steel sheet is heated from 400°C to the annealing temperature at an average heating rate of 1.0°C / sec or more, held at the annealing temperature for 10 to 600 seconds, then cooled from the annealing temperature to Ar3 point at an average cooling rate of 10°C / sec or more, cooled from Ar3 point to (Ar3 point - 80°C) at an average cooling rate of 1 to 10°C / sec, cooled from (Ar3 point - 80°C) to a cooling stop temperature of 260°C or less at an average cooling rate of 10°C / sec or more, and then continuously annealed by holding at a holding temperature of 150 to 260°C for 20 to 1500 seconds. In the present invention, the temperature specified in each step refers to the surface temperature of the slab (steel slab) or steel plate.

[0064] Hot rolling Heating temperature: Slab surface temperature 1100℃ or higher Heating time (slab heating time): 30 minutes or more In the slab heating before hot rolling, the steel slab is held at a heating holding temperature (slab heating holding temperature) of 1100°C or more at the slab surface temperature for 30 minutes or more to promote solid solution of precipitates such as B-based precipitates, thereby reducing the size and number of precipitates. The heating holding temperature is preferably 1150°C or more. The heating holding temperature is preferably 1250°C or less. The time for which the slab is held at the heating temperature (holding time (slab heating holding time)) is preferably 40 minutes or more. The holding time is preferably 50 minutes or less.

[0065] Residence time at 900-1000℃: 20 seconds to 150 seconds In hot rolling, the slab is held at 900 to 1000°C for 20 seconds or more and 150 seconds or less. Increasing the holding time in the temperature range of 900 to 1000°C generates precipitates mainly composed of BN, which coarsen. The precipitates generated in these temperature ranges are difficult to dissolve by annealing heating, which reduces the amount of dissolved B after annealing. If the holding time exceeds 150 seconds, it is not possible to obtain an amount of dissolved B effective in suppressing delayed fracture. Therefore, the holding time is 150 seconds or less, preferably 120 seconds or less, and more preferably 100 seconds or less. On the other hand, if the residence time is less than 20 seconds, the texture may become non-uniform. Therefore, the residence time is 20 seconds or more. The residence time is preferably 30 seconds or more.

[0066] Finish rolling temperature: 850℃ or higher In the hot finish rolling, the finish rolling temperature (FT) is set to 850° C. or higher in order to suppress non-uniformity of the hot rolled structure, and is preferably 870° C. or higher. The finish rolling temperature is preferably 930° C. or lower.

[0067] Average cooling rate in the range from the finishing rolling temperature to 650°C (first average cooling rate): 40°C / sec or more In the cooling process after hot finish rolling, the average cooling rate in the range from the finish rolling temperature to 650°C is set to 40°C / sec or more. In the temperature range from the finish rolling temperature to 650°C, B segregates at the grain boundaries with the recrystallization of austenite, and Fe 23 (C,B)6 precipitates. Fe 23 In order to minimize the precipitation of (C, B) 6, the average cooling rate (first average cooling rate) is set to 40° C. / sec or more, and preferably 60° C. / sec or more. The average cooling rate is preferably 500° C. / sec or less, and more preferably 300° C. / sec or less. The average cooling rate in the hot rolling process (first average cooling rate) is defined as "(temperature at the start of cooling (finish rolling temperature) (℃) - temperature at the end of cooling (℃) (650℃)) / cooling time from the start of cooling to the end of cooling (seconds)."

[0068] Winding temperature: 650℃ or less After cooling to 650°C, the wire is further cooled as necessary and then coiled. If the coiling temperature exceeds 650°C, the wire may be damaged. 23 Since the precipitation of (C, B)6 is promoted, the delayed fracture resistance property is deteriorated. Therefore, the coiling temperature is set to 650°C or less. The coiling temperature is preferably 600°C or less. Moreover, the coiling temperature is preferably 500°C or more.

[0069] Cold rolling Rolling reduction rate: 40% or more If the reduction rate (cumulative reduction rate (cold rolling rate)) in cold rolling is 40% or more, the recrystallization behavior and texture orientation in the subsequent continuous annealing can be stabilized. If the reduction rate is less than 40%, some of the austenite grains during annealing may become coarse, which may result in a decrease in strength. In addition, the reduction rate is preferably 80% or less.

[0070] Continuous Annealing Average heating rate from 400℃ to annealing temperature: 1.0℃ / sec or more After cold rolling, the steel sheet is annealed and tempered in a continuous annealing line (CAL), and then subjected to temper rolling if necessary. Fe 23 (C,B)6 is generated in the ferrite region during annealing and coarsens, so Fe 23In order to reduce (C,B)6 and fully obtain the effect of grain boundary strengthening by B, it is necessary to increase the average heating rate from 400°C to the annealing temperature. From this viewpoint, the average heating rate at 400°C or higher is 1.0°C / sec or higher. The average heating rate from 400°C to the annealing temperature is preferably 1.5°C / sec or higher, more preferably 3.0°C / sec or higher. Moreover, the above average heating rate is preferably 10°C / sec or lower. The average heating rate here means "annealing temperature (°C) - 400 (°C)) / heating time (minutes) from 400°C to the annealing temperature, which will be described later."

[0071] Annealing temperature: 830~950℃ Heating time (holding time at annealing temperature): 10 seconds to 600 seconds Undissolved Fe remaining after annealing 23 In order to sufficiently reduce precipitates such as (C, B)6, annealing is performed at a high temperature for a long time. Specifically, the annealing temperature must be 830° C. or higher. The annealing temperature is preferably 840° C. or higher, and more preferably 850° C. or higher. On the other hand, annealing at a temperature above 950°C causes the prior austenite grain size to become coarse, and the grain size of the ferrite formed thereafter also becomes coarse. If the annealing temperature exceeds 950°C, the desired average grain size of ferrite cannot be obtained, so the annealing temperature is set to 950°C or less. The annealing temperature is preferably 900°C or less. Moreover, an excessively long soaking time (holding time) also leads to coarsening of the prior austenite grain size, and coarsening of the average grain size of ferrite. Therefore, the soaking time is set to 600 seconds or less. The soaking time is preferably 540 seconds or less, and more preferably 480 seconds or less. On the other hand, the remaining undissolved Fe 23 The soaking time is set to 10 seconds or more in order to sufficiently reduce precipitates such as (C, B) 6. The soaking time is preferably 30 seconds or more, and more preferably 60 seconds or more.

[0072] Average cooling rate from annealing temperature to Ar3 point (second average cooling rate): 10℃ / sec or more Average cooling rate from Ar3 point to (Ar3 point - 80℃) (third average cooling rate): 1 to 10℃ / sec Average cooling rate from (Ar3 point -80℃) to the cooling stop temperature of 260℃ or less (4th average cooling rate): 10℃ / sec or more In order to obtain a structure in which the area ratio of martensite is 85% or more and less than 95% and the area ratio of ferrite is 5% or more and 15% or less while keeping the number density A of precipitates in the desired range, cooling is performed from the annealing temperature to the Ar3 point (°C) at an average cooling rate of 10°C / sec or more (second average cooling rate), cooling is performed from the Ar3 point (°C) to (Ar3 point -80°C) at an average cooling rate of 1 to 10°C / sec (third average cooling rate), and cooling is performed from (Ar3 point -80°C) to a cooling stop temperature of 260°C or less at an average cooling rate of 10°C / sec or more (fourth average cooling rate).

[0073] Here, the second average cooling rate is "(annealing temperature (° C.)-Ar3 point (° C.)) / cooling time from the annealing temperature to the Ar3 point (seconds)". In addition, the third average cooling rate is "(Ar3 point (°C)-(Ar3 point-80) (°C)) / cooling time (seconds) from Ar3 point (°C) to (Ar3 point-80) (°C)". In addition, the fourth average cooling rate is "((Ar3 point-80)(℃)-cooling stop temperature (℃) below 260℃) / cooling time (seconds) from (Ar3 point-80℃) to the cooling stop temperature below 260℃." The Ar3 point can be calculated by the following formula: Ar3 points (℃)=910-310×C-80×Mn-20×Cu-15×Cr-55×Ni-80×Mo In addition, the element symbols in the formulas represent the content (mass%) of each element. Elements that are not contained are calculated as 0 (zero).

[0074] When the average cooling rate from the annealing temperature to the Ar3 point (the second average cooling rate) is less than 10°C / sec, Fe 23 (C,B)6 is excessively generated, and the delayed fracture resistance property is deteriorated. Therefore, the average cooling rate from the annealing temperature to the Ar3 point is set to 10°C / sec or more. The second average cooling rate is preferably 20° C. / sec or more, and more preferably 30° C. / sec or more. The second average cooling rate is preferably 150° C. / sec or less, and more preferably 100° C. / sec or less.

[0075] If the average cooling rate from the Ar3 point to (Ar3 point - 80°C) (the third average cooling rate) exceeds 10°C / sec, ferrite is not sufficiently formed and the delayed fracture resistance deteriorates. Therefore, the average cooling rate from the Ar3 point to (Ar3 point - 80°C) (the third average cooling rate) is set to 10°C / sec or less. On the other hand, if the average cooling rate from the Ar3 point to (Ar3 point - 80°C) (third average cooling rate) is less than 1°C / sec, ferrite will be excessively generated, so the average cooling rate from the Ar3 point to (Ar3 point - 80°C) (third average cooling rate) is set to 1°C / sec or more. The third average cooling rate is preferably 3°C / sec or more, more preferably 5°C / sec or more.

[0076] If the average cooling rate from (Ar3 point - 80°C) to the cooling stop temperature of 260°C or less (fourth average cooling rate) is less than 10°C / sec, a large amount of bainite, ferrite and pearlite are formed, and sufficient strength and delayed fracture resistance cannot be obtained. Therefore, the average cooling rate from (Ar3 point - 80°C) to 260°C or less is set to 10°C / sec or more. The fourth average cooling rate is preferably 70°C / sec or more. The fourth average cooling rate is more preferably 100°C / sec or more, and further preferably 200°C / sec or more. The fourth average cooling rate is preferably 1000° C. / sec or less, and more preferably 750° C. / sec or less.

[0077] Furthermore, if the cooling stop temperature exceeds 260°C, upper and lower bainite are generated, and the amount of retained austenite and fresh martensite increases, making it difficult to obtain sufficient delayed fracture resistance. Therefore, the cooling stop temperature is set to 260°C or lower. The cooling stop temperature is preferably 250°C or lower, and more preferably 240°C or lower.

[0078] Holding temperature: 150~260℃ Holding time: 20~1500 seconds The carbides distributed inside martensite are carbides that are formed during low-temperature holding after quenching. In order to ensure excellent delayed fracture resistance and a tensile strength of 1470 MPa or more (TS≧1470 MPa), it is necessary to properly control the formation of the above carbides. To achieve this, it is necessary to control the holding temperature to 150 to 260°C and the holding time to 20 to 1500 seconds. If the holding temperature is lower than the lower limit of 150° C. or the holding time is short, the distribution density of carbides within the transformed phase becomes insufficient, resulting in deterioration of delayed fracture resistance. On the other hand, if the holding temperature is higher than the upper limit of 260°C, the coarsening of carbides within grains and at block grain boundaries becomes significant, and the delayed fracture resistance may deteriorate. Also, if the holding time exceeds 1500 seconds, the coarsening of carbides within grains and at block grain boundaries becomes significant, and the delayed fracture resistance may deteriorate. Therefore, in the present invention, in continuous annealing, the holding temperature is 150 to 260°C and the holding time is 20 to 1500 seconds. The holding temperature is preferably 250° C. or lower, more preferably 240° C. or lower. The retention time is preferably 50 seconds or more, and more preferably 100 seconds or more. The retention time is preferably 1300 seconds or less, more preferably 1000 seconds or less.

[0079] The steel sheet thus obtained can be subjected to skin pass rolling from the viewpoint of stabilizing press formability, such as adjusting the surface roughness and flattening the sheet shape. In this case, the skin pass elongation is preferably 0.1% or more. Also, the skin pass elongation is preferably 1.0% or less. In this case, it is preferable to use a dull roll as the skin pass roll and adjust the roughness Ra of the steel sheet to 0.8 μm or more from the viewpoint of flattening the shape. Also, it is preferable to adjust the roughness Ra of the steel sheet to 1.8 μm or less.

[0080] The obtained steel sheet may be subjected to a plating treatment. That is, after the continuous annealing, the surface of the steel sheet may be subjected to a plating treatment. By performing the plating treatment, a steel sheet having a plating layer on the surface is obtained.

[0081] As described above, according to the present invention, the delayed fracture resistance of high-strength cold-rolled steel sheets is significantly improved, and the application of high-strength steel sheets contributes to improving the strength of parts and reducing their weight. The steel sheets of the present invention preferably have a thickness of 0.5 mm or more. Also, the thickness is preferably 2.0 mm or less.

[0082] Next, the member of the present invention and the method for producing the same will be described.

[0083] The member of the present invention is obtained by subjecting the steel plate of the present invention to at least one of forming and joining. Also, the method for producing the member of the present invention includes a step of subjecting the steel plate of the present invention to at least one of forming and joining to obtain the member.

[0084] The steel plate of the present invention has a tensile strength of 1470 MPa or more and has excellent delayed fracture resistance. Therefore, the member obtained by using the steel plate of the present invention also has high strength and is superior in delayed fracture resistance compared to conventional high strength members. Furthermore, the use of the member of the present invention allows weight reduction. Therefore, the member of the present invention can be suitably used, for example, for vehicle body frame parts.

[0085] The forming process may be performed by a general processing method such as pressing, without any restrictions. The joining process may be performed by a general welding method such as spot welding or arc welding, riveting, or crimping, without any restrictions. EXAMPLES

[0086] The following describes an embodiment of the present invention. Steel having the composition shown in Table 1 was melted and cast into a slab. This slab was subjected to the heat treatment and rolling shown in Table 2 to obtain a steel plate having a thickness of 1.4 mm.

[0087] Specifically, a slab having each component composition was held at the heating holding temperature shown in Table 2 for the heating holding time shown in Table 2, then the residence time at 900 to 1000°C shown in Table 2 was set, hot finish rolling was performed at the finish rolling temperature shown in Table 2, cooling was performed at the first average cooling rate shown in Table 2, and coiling was performed at the coiling temperature shown in Table 2 to produce a hot-rolled steel sheet. Thereafter, the hot-rolled steel sheets were cold-rolled at the reduction ratios (cold rolling reduction ratios) shown in Table 2 to obtain cold-rolled steel sheets. The cold-rolled steel sheet was then heated to the annealing temperature shown in Table 2 at the average heating rate shown in Table 2, held for the soaking time shown in Table 2, and then cooled to 260°C or less under the cooling conditions shown in Table 2 (second average cooling rate, third average cooling rate, fourth average cooling rate, cooling stop temperature), reheated as necessary, and subjected to continuous annealing at the holding temperature shown in Table 2 for the holding time shown in Table 2.

[0088] For No. 2, the obtained steel sheet was subjected to electroplating to obtain a steel sheet having a Zn plating layer formed thereon.

[0089] [Table 1]

[0090] [Table 2]

[0091] The metal structure of the obtained steel sheets was quantified by the method described above, and further, a tensile test and a delayed fracture resistance evaluation test were performed. Specifically, the tissue measurements were performed as follows. The area ratios of martensite, bainite, and ferrite were measured by polishing the L-section of the steel plate (a vertical section parallel to the rolling direction) and then etching it with nital, and observing four fields of view in an area of ​​50 μm × 65 μm at a magnification of 2000 times using an SEM at a position 1 / 4 of the thickness from the steel plate surface, and performing image analysis on the photographed structure. Here, martensite and bainite refer to structures that appear gray or white when viewed using an SEM. Bainite has the following characteristics. That is, it has an aspect ratio of 2.5 or more and a plate-like form, and is a slightly black structure compared to martensite. The width of the above plates is 0.3 to 1.7 μm. The distribution density of carbides with diameters of 10 to 200 nm inside the bainite is 0 to 3 pieces / μm. 2 On the other hand, ferrite is an area that shows a black contrast in SEM. Note that martensite and bainite contain small amounts of carbides, nitrides, sulfides, and oxides inside, but since it is difficult to exclude these, the area ratio of the area including these was used as the area ratio.

[0092] The amount of retained austenite (retained gamma) was measured by chemically polishing the surface of the steel sheet with oxalic acid for 200 μm, and the amount was measured by the X-ray diffraction intensity method. It was calculated from the integrated intensity of the (200)α, (211)α, (220)α, (200)γ, (220)γ, and (311)γ diffraction peaks measured with Mo-Kα radiation.

[0093] The average grain size of ferrite was obtained by polishing the L-section of the steel plate (a vertical section parallel to the rolling direction) and etching it with nital, and observing 10 fields of view in an area of ​​50 μm × 65 μm at a magnification of 2000 times using an SEM at a position 1 / 4 of the thickness from the steel plate surface, and performing image analysis of the photographed microstructure to determine the circle equivalent diameter.

[0094] The method for measuring the area ratio of ferrite precipitated on the prior austenite grain boundaries is as follows. First, the L-section of the steel plate was mirror-polished using colloidal silica vibration polishing, and then electron backscatter diffraction (EBSD) measurements were performed to obtain local crystal orientation data for 10 fields of view at a 1 / 4 thickness position from the steel plate surface. The step size was 0.10 μm, and the measurement area was 50 μm x 50 μm. After cleanup processing using analysis software OIMAnalysis 7, the obtained local orientation data was analyzed to determine the prior austenite grain boundaries. The cleanup process involved replacing the orientation and CI value of pixels with a CI value of 0.2 or less with that of the neighboring pixel with the highest CI value. Specifically, the cleanup process was performed using the Neighbor CI Correlation function of the analysis software with the parameter Minimum CoufidenceIndex set to 0.2. A map of grain boundaries with crystal orientation differences of 20° or more and 50° or less was created, and these interfaces were determined to be prior austenite grain boundaries. After EBSD measurement, the L-section of the steel plate was etched with nital, and the same 10 fields of view as those used for EBSD were photographed with an SEM at a magnification of 3000x. When the photographed SEM image was overlaid on the prior austenite grain boundary map of the same field of view, the ferrite present on the prior austenite grain boundaries was identified, and the area ratio was measured. To observe the same field of view using EBSD and SEM, an indentation was made in advance at the observation position on the steel plate using a Vickers hardness tester to mark the observation position.

[0095] The number density A of precipitates with a circle equivalent diameter of 500 nm or more is measured after polishing the L cross section (vertical cross section parallel to the rolling direction) of the steel sheet, in the region from the 1 / 5 position to the 4 / 5 position of the sheet thickness of the steel sheet, that is, in the region from the 1 / 5 position of the sheet thickness from the steel sheet surface to the 4 / 5 position, including the center of the sheet thickness, within 2 mm 2The area was photographed continuously with an SEM, and the number of such precipitates was counted from the photographed SEM photographs. The magnification for photographing was 2000 times. When analyzing the components of individual inclusion particles, the individual inclusion particles were magnified 10000 times and the above precipitates were analyzed. Here, precipitates with a circle equivalent diameter of 500 nm or more were classified as Fe 23 (C,B)6 and other precipitates containing B were examined for the presence or absence of a B peak by elemental analysis using energy dispersive X-ray spectroscopy (EDS) at an accelerating voltage of 3 kV. When a B peak was present, it was determined that the above precipitates were present.

[0096] For the tensile test, a JIS No. 5 tensile test piece was cut out at 1 / 4 of the coil width so that the direction perpendicular to the rolling was the longitudinal direction, and a tensile test (in accordance with JIS Z2241 (2022)) was performed to evaluate the tensile strength TS. A tensile strength TS of 1470 MPa or more was deemed to have passed.

[0097] The delayed fracture resistance was evaluated as follows. A strip test piece was taken from the obtained steel sheet (coil) at 1 / 4 of the coil width in the width direction, with a length of 100 mm in the direction perpendicular to the rolling direction and 30 mm in the rolling direction. The cut end face on the long side with a length of 100 mm was sheared, and the sheared state (without machining to remove burrs) was bent so that the burrs were on the outer periphery of the bend, and the test piece shape at the time of bending was maintained and fixed with bolts. The shearing clearance was 13%, and the rake angle was 1°. The bending was performed with a tip bending radius of 10 mm and an inner angle of the bend apex of 90 degrees (V-bend). The punch had a tip radius R equal to the tip bending radius R and was U-shaped (the tip R part was semicircular and the punch body had a thickness of 2R), and the die had a corner R of 30 mm. The punch was adjusted to a depth into which the steel plate was pressed, and the bending angle at the tip (angle at the inner side of the bending apex) was formed to 90 degrees (V-shape). The test piece was clamped and tightened with a hydraulic jack so that the distance between the flange ends of the straight piece during bending was the same as when the straight piece was bent (to cancel out the opening of the straight piece due to springback), and the bolts were fastened in that state. The bolts were passed through and fixed in an elliptical (minor axis 10 mm, major axis 15 mm) hole that was previously provided 10 mm inside from the short edge of the strip test piece. The obtained test piece after bolt fastening was immersed in a solution in which 0.1 mass% ammonium thiocyanate aqueous solution and McIlvaine buffer solution were mixed in a mass ratio of 1:1 and the pH was adjusted to 8.0 and a solution in which the pH was adjusted to 7.4, respectively, to perform a delayed fracture resistance evaluation test. At this time, the temperature of the solution was 20°C, and the test piece had a surface area of ​​1 cm2. 3 The amount of liquid per test was 20 ml. After 48 hours, the presence or absence of visually visible cracks (length 1 mm or more) was checked, and specimens in which no cracks were observed in the solution adjusted to pH 8.0 were judged to have excellent delayed fracture resistance. Furthermore, specimens in which no cracks were observed in the solution adjusted to pH 7.4 were judged to have particularly excellent delayed fracture resistance. In Table 3, specimens in which no cracks were observed in the solution adjusted to pH 8.0 are indicated with a "〇 (pass)", and specimens in which no cracks were observed even in the solution adjusted to pH 7.4 are indicated with a "◎ (pass)". On the other hand, if cracks were observed in the solution adjusted to pH 8.0, they were indicated with an "X (fail)".

[0098] The structure and properties of the obtained steel sheets are shown in Table 3.

[0099] [Table 3]

[0100] The steel plates within the scope of the present invention had high strength and excellent delayed fracture resistance. Among the steel sheets within the scope of the present invention, the steel sheets having a tensile strength of 1800 MPa or less were evaluated as "A (pass)" and were particularly excellent in terms of delayed fracture resistance. In addition, even if the tensile strength was more than 1,800 MPa and not more than 1,900 MPa, the steel plate in which the area ratio of ferrite precipitated on the prior austenite grain boundaries to the total ferrite was 50% or more was evaluated as having excellent delayed fracture resistance, being rated as "◎ (pass)." On the other hand, in the comparative examples, at least one of the tensile strength and the delayed fracture resistance was insufficient.

[0101] In addition, it was found that the components obtained by forming and joining the steel plates of the present invention have high strength and excellent resistance to delayed fracture, similar to the steel plates of the present invention, because the steel plates of the present invention have high strength and excellent resistance to delayed fracture.

Claims

1. In mass percent, C: 0.15% or more and 0.45% or less, Si: 2.0% or less, Mn: 4.0% or less, P: 0.10% or less, S: 0.01% or less, sol. Al: 0.50% or less, N: 0.010% or less, B: Contains 0.0008% or more and 0.0100% or less, The balance is Fe and unavoidable impurities, The area ratio of martensite to the entire structure is 85% or more and less than 95%, The area ratio of ferrite to the entire structure is 5% or more and 15% or less, The steel has a steel structure in which the average grain size of ferrite is 10 μm or less, A steel sheet in which the number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula (1). A (pieces / mm 2 )≦ 8.5×10 5 ×[B] ……Formula (1) Here, [B] represents the B content (mass %).

2. 2. The steel sheet according to claim 1, wherein 50% or more of the ferrite is precipitated on prior austenite grain boundaries, in terms of area ratio.

3. The composition further includes, in mass%, Cu: 1.00% or less, Cr: 1.00% or less, Nb: 0.10% or less, Ti: 0.10% or less, V: 0.50% or less, Mo: 0.50% or less, Ni: 1.00% or less, Sb: 0.10% or less, Sn: 0.10% or less, As: 0.10% or less, Ta: 0.10% or less, Ca: 0.020% or less, Mg: 0.020% or less, Zn: 0.020% or less, Co: 0.020% or less, Zr: 0.020% or less, W: 0.020% or less, The steel plate according to claim 1, further comprising one or more selected from the following: REM: 0.020% or less.

4. The composition further includes, in mass%, Cu: 1.00% or less, Cr: 1.00% or less, Nb: 0.10% or less, Ti: 0.10% or less, V: 0.50% or less, Mo: 0.50% or less, Ni: 1.00% or less, Sb: 0.10% or less, Sn: 0.10% or less, As: 0.10% or less, Ta: 0.10% or less, Ca: 0.020% or less, Mg: 0.020% or less, Zn: 0.020% or less, Co: 0.020% or less, Zr: 0.020% or less, W: 0.020% or less, The steel plate according to claim 2, further comprising one or more selected from the following: REM: 0.020% or less.

5. The steel sheet according to any one of claims 1 to 4, which has a plating layer on a surface of the steel sheet.

6. A member made using the steel plate according to any one of claims 1 to 4.

7. A member made using the steel plate according to claim 5.

8. A steel slab having the composition according to claim 1 or 3 is heated and held at a slab surface temperature of 1100° C. or higher for 30 minutes or more, and then Hot finish rolling is performed under conditions of a residence time at 900 to 1000°C of 20 seconds or more and 150 seconds or less and a finish rolling temperature of 850°C or more; Cooling is performed at an average cooling rate of 40° C. / sec or more in the range from the finish rolling temperature to 650° C., Thereafter, the hot-rolled steel sheet is obtained by coiling the steel sheet at a coiling temperature of 650°C or less. The hot-rolled steel sheet is cold-rolled at a rolling reduction of 40% or more to obtain a cold-rolled steel sheet; The annealing temperature is set to 830 to 950 ° C., and the cold-rolled steel sheet is heated from 400 ° C. to the annealing temperature at an average heating rate of 1.0 ° C. / sec or more, After holding at the annealing temperature for 10 seconds or more and 600 seconds or less, From the annealing temperature to Ar 3 Cooling to a temperature of 10° C. / s or more at an average cooling rate of 10° C. / s or more; Ar 3 From the point (Ar 3 Cooling to a temperature of −80° C. at an average cooling rate of 1 to 10° C. / sec, (Ar 3 Cooling is performed at an average cooling rate of 10°C / sec or more from the cooling stop temperature (point -80°C) to a cooling stop temperature of 260°C or less, Then, continuous annealing is performed at a holding temperature of 150 to 260°C for 20 to 1500 seconds. A method for manufacturing a steel sheet having a steel structure in which the area ratio of martensite to the entire structure is 85% or more and less than 95%, the area ratio of ferrite to the entire structure is 5% or more and 15% or less, and the average crystal grain size of ferrite is 10 μm or less, the number density A of precipitates having an equivalent circle diameter of 500 nm or more satisfies the following formula (1), and further optionally, 50% or more of the ferrite is ferrite precipitated on prior austenite grain boundaries, in terms of area ratio. A (pieces / mm2)≦8.5×105×[B]...Formula (1) Here, [B] represents the B content (mass %).

9. The method for producing a steel sheet according to claim 8, further comprising the step of: plating a surface of the steel sheet after the continuous annealing.

10. A method for manufacturing a component, comprising a step of subjecting the steel plate according to any one of claims 1 to 4 to at least one of forming and joining to form a component.

11. A method for manufacturing a component, comprising the step of subjecting the steel plate according to claim 5 to at least one of forming and joining to form a component.

Citation Information

Patent Citations

  • Post-treatment of plated steel sheet

    JP1988088085A

  • High-strength cold-rolled steel sheet with excellent hydrogen embrittlement resistance and workability.

    JP4712882B2

  • High-strength cold rolled steel sheet exhibiting excellent material-quality uniformity, and production method therefor

    WO2015151428A1

  • Thin steel sheet, and production method therefor

    WO2018030501A1

  • Steel sheet, member, method for producing said steel sheet, and method for producing said member

    WO2023008003A1